Liberating the classroom: Ethnographic elements in liberation theologies curricula - Hankela, Elina (Teaching theology and religion, 2020)
A lively conversation has arisen in recent years among theologians concerning ethnographic theology. While liberation theologians have scarcely participated in it, an emphasis on lived experience - which ethnography aims to understand - lies at the heart of theologies of liberation. This article addresses the question of employing ethnographic elements in teaching liberation theologies by bringing higher education scholarship into conversation with the liberation theological discourse. It is argued that ethnographic methods, if framed within the liberationist discourse, provide effective tools for liberation theologies curricula, because such methods are in line with the liberationist threshold concept of interlocution. In a secular university, ethnographic methods can, furthermore, provide the student with epistemological distance from the truths of liberation theologies, while the inclusion of ethnography in theologies curricula can be conceptualized as an aspect of decolonizing education. Although the article focuses on teaching liberation theologies, the general principles can also be applied to teaching theology and religion more broadly.